Increased Blood Pressure Causes Lymphatic Endothelial Dysfunction via Oxidative Stress in Spontaneously Hypertensive Rats. Issue 2 (August 2020) - Mukohda, Masashi; Mizuno, Risuke; Ozaki, Hiroshi
Abstract : The lymphatic system is involved in the pathogenesis of edema, inflammation, and cancer metastasis. Because lymph vessels control fluid electrolytes and volume balance, changes in lymphatic activity can be expected to alter systemic blood pressure. This study examined possible changes in lymphatic contractile properties in spontaneously hypertensive rats (SHR). Thoracic ducts isolated from 10- to 12-week-old SHR exhibited either decreased acetylcholine-induced endothelium-dependent relaxation or sodium nitroprusside-induced endothelium-independent relaxation compared with age-matched Wister-Kyoto rats. The impairment in acetylcholine responsiveness was more pronounced than sodium nitroprusside responsiveness. N-Nitro-L-arginine methyl ester, a nitric oxide synthase inhibitor blunted acetylcholine-induced relaxation in Wister-Kyoto rats, indicating an involvement of endothelial nitric oxide production. Endothelial dysfunction in lymph vessels of SHR was attenuated by tempol (a superoxide dismutase mimetic), apocynin, or VAS-2870 (NADPH oxidase inhibitors). Consistent with these observations, nitrotyrosine levels were significantly elevated in SHR, indicative of increased oxidative stress. In addition, protein expression of NADPH oxidase 2 and phosphorylation of p47 phox (Ser345) were significantly increased in SHR. Further, SB203580 (a p38 MAPK inhibitor) restored the acetylcholine-induced relaxation in SHR. It is notable that 4-week-old SHR, which exhibited normal blood pressure, did not show any decreased activity of acetylcholine- or sodium nitroprusside-induced relaxation. Additionally, antihypertensive treatment of 4-week-old SHR with hydrochlorothiazide and reserpine or hydrochlorothiazide and hydralazine for 6 weeks completely restored lymphatic endothelial dysfunction. We conclude that contractile activity of lymphatic vessels is functionally impaired with the development of increasing blood pressure, which is mediated through increased oxidative stress via the p38 MAPK/NADPH oxidase 2 pathway. Abstract : Supplemental Digital Content is available in the text.